EB coating for automotive trim
By applying EB coatings of polyurethane modified acrylic prepolymer, ethylene glycol diacrylate graft monomer and ferromanganese LDHs on PMMA blister sheets, the wear resistance and scratch resistance of PMMA blister sheets are solved. The problem of insufficient achieves higher wear and scratch resistance, improving its performance in automotive interior applications.
Patent Information
- Application Number
- CN202411533087.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
PMMA blister plates have poor surface wear resistance and scratch resistance in automotive interior applications, which limits their wide application.
The EB coating with a combination of polyurethane modified acrylic prepolymer, ethylene glycol diacrylate graft monomer and ferromanganese LDHs is used to improve the surface performance of the sheet through electron beam radiation curing technology.
The coating is significantly improved and scratch resistance is made, making PMMA blister sheets more reliable and durable in automotive interior applications.
Smart Images

Figure BDA0005110869120000061 
Figure BDA0005110869120000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of automobile parts, and in particular relates to an EB coating of a thick sheet of blister board for automobile interior decoration. Background Art
[0002] With the continuous development of intelligent and green energy in the automotive industry, the time for automobile renewal is becoming more and more frequent, and various models are constantly replaced. At the same time, the interior and exterior decoration and shell parts of the car are updated rapidly. In order to adapt to the current situation and reduce the cost of component molds and time loss, automobiles have ushered in a large number of thick sheet plastic forming processes to quickly produce automotive parts.
[0003] Meanwhile, in the summer, when the outdoor temperature is high, the temperature inside a closed car can rise rapidly. Especially under direct sunlight, the temperature inside the car can reach very high levels. Generally, if the outdoor temperature is 35 degrees Celsius, the temperature inside the car can reach more than 70 degrees after being exposed to the sun for a long time, and even close to 90 degrees in extreme cases. This is because the interior of the car is mostly made of dark heat-absorbing materials, and the closed environment inside the car makes it impossible to effectively dissipate heat, resulting in a sharp rise in temperature, including problems such as softening, deformation and cracking of components caused by direct ultraviolet rays.
[0004] Thick sheet blister is widely used in the automotive industry, covering the manufacture of multiple parts, especially interior parts, which can specifically include dashboards, center consoles, door panels, etc. These parts not only increase the comfort and beauty of the car interior, but also improve the convenience of use. However, the disadvantages of the automotive thick sheet blister process mainly include high cost, difficulty in processing, and the need for professional equipment and technology. In addition, the performance of thick sheet blister is also limited by the characteristics of the material. Take PMMA blister sheet as an example. It is a sheet made of methyl methacrylate (PMMA) as raw material, also known as acrylic blister sheet. It has good transparency and brightness. It is often used in high-end furniture and decoration applications. It has gradually been used in automotive interior materials. PMMA blister sheet has the advantages of high transparency, good light transmittance, smooth surface, superior texture, strong impact resistance, and not easy to break. However, it also has the disadvantages of difficulty in processing, relatively poor wear resistance and scratch resistance. In particular, the disadvantages of poor wear resistance and scratch resistance on the surface of the sheet seriously restrict the application of PMMA blister sheet in automotive interior. Summary of the invention
[0005] The purpose of the present invention is to provide an EB coating for thick sheet blister board for automobile interior decoration, especially an EB coating for PMMA blister board, based on the prior art, which can not only maintain the characteristics of PMMA blister board, but also greatly improve the surface performance of PMMA blister board, so that it can be more conveniently used in the field of automobile interior decoration.
[0006] The purpose of the present invention can be achieved by the following measures:
[0007] An EB coating for automobile interior decoration comprises a polyurethane modified acrylic prepolymer, an ethylene glycol diacrylate grafted monomer and manganese iron LDHs; wherein, in parts by weight, the polyurethane modified acrylic prepolymer is used in an amount of 50-90 parts, the ethylene glycol diacrylate grafted monomer is used in an amount of 5-25 parts, and the manganese iron LDHs is used in an amount of 0.1-1 parts; the manganese iron LDHs is a layered double metal hydroxide obtained by hydrothermal reaction of a manganese salt and a trivalent iron salt under the action of NaOH and sodium nitrite.
[0008] The amount of the polyurethane modified acrylic prepolymer used in the present invention is preferably 70-85 parts, more preferably 75-85 parts.
[0009] The ethylene glycol diacrylate grafting monomers in the present invention include ethylene glycol diacrylate, diethylene glycol diacrylate, and triethylene glycol diacrylate, and the usage amount thereof is preferably 10-25 parts, more preferably 15-25 parts.
[0010] The dosage of ferromanganese LDHs in the present invention is preferably 0.5-1 part.
[0011] A specific preparation method of the ferromanganese LDHs of the present invention is: mixing manganese salt and trivalent iron salt in deionized water, then adding NaOH solution and sodium nitrite to mix, and then placing in a hydrothermal reactor, hydrothermally reacting at 100-125° C., filtering after the reaction, and drying at 90-110° C. to obtain.
[0012] The manganese salt in the present invention may be manganese nitrate or manganese sulfate, and the ferric iron salt may be ferric sulfate or ferric nitrate.
[0013] In the method for preparing ferromanganese LDHs, preferably, after the manganese salt and the trivalent iron salt are mixed in deionized water, Mn 2+ The molar concentration of Fe 3+ The amount of NaOH used is 2-3 times that of Mn 2+ with Fe 3+ 1-1.2 times the sum of the molar amounts, Mn 2+ with Fe 3+ The sum of the molar amounts is 3-4 times the molar amount of sodium nitrite.
[0014] The composition of the present invention also includes a ketone or ester solvent, such as acetone or γ-butyrolactone, for dispersing the ferromanganese LDHs.
[0015] The coating of the present invention may further include active diluents, fillers, dispersants, additives, etc. In a preferred embodiment, it may further include 5-25 parts of active diluents, 1-5 parts of fillers, 1-5 parts of dispersants, and 0.5-2 parts of additives.
[0016] The auxiliary agent in the present invention can be one or more of a leveling agent, a defoaming agent, a light stabilizer, an antistatic agent, an antibacterial agent, etc. For example, the leveling agent can be propoxylated neopentyl glycol diacrylate. The defoaming agent can be polyacrylamide.
[0017] The preparation method of the EB coating for automobile interior of the present invention comprises: firstly mixing a polyurethane modified acrylic prepolymer, an ethylene glycol diacrylate grafting monomer and ferromanganese LDHs (or a dispersion containing ferromanganese LDHs) and then stirring at high speed, then adding one or more of an active diluent, a filler, a dispersant and an auxiliary agent, and dispersing in a high-speed disperser at 1500-2500 rpm for 20-100 minutes to obtain the coating.
[0018] The conditions for curing the surface coating of the automobile interior EB coating of the present invention by electron beam radiation curing are as follows: radiation voltage is 380-420 KeV; electron beam dose is 30-45 KGy; beam current is 90-120 mA; and radiation curing temperature is 20-30°C.
[0019] The EB coating for automobile interior decoration of the present invention is particularly suitable for PMMA blister sheets. According to the requirements of thick blister sheets for automobile interior decoration, the thickness of the coating applied on the sheet surface can be adjusted, for example, the coating thickness is 100-300 μm.
[0020] Before coating, the surface of the plate can be pre-treated by grinding, sandblasting or the like to remove burrs, protrusions, rough edges, etc. on the surface of the plate.
[0021] Beneficial effects of the present invention: The EB coating for automobile interior of the present invention can greatly improve the wear resistance and scratch resistance of the coating while maintaining adhesion and hardness when using a trace amount of manganese iron LDHs material, so that the automobile interior PMMA thick sheet blister board can be used in most areas of the earth, providing an excellent choice for high-end automobile interior materials. DETAILED DESCRIPTION
[0022] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0023] Example 1: Preparation of ferromanganese LDHs dispersion M1
[0024] Manganese nitrate and ferric sulfate are mixed in deionized water to obtain a mixed ion solution, wherein Mn 2+ The concentration of Fe is 0.6 mol / L. 3+The concentration is 0.2mol / L; the mixed ion solution is mixed with an equal volume of a NaOH solution with a concentration of 0.8mol / L, and then sodium nitrite is added to mix and the concentration of nitrite is adjusted to 0.2mol / L; placed in a hydrothermal reactor, hydrothermally reacted at 120°C for 6h, cooled to room temperature and then filtered, washed with water until neutral, and dried at 100°C for 8h to obtain manganese iron LDHs with a particle size of 60-110nm.
[0025] 2 g of ferromanganese LDHs prepared by the above method was dispersed in 40 ml of γ-butyrolactone, and ultrasonically dispersed for 15 min after high-speed stirring. The mixture was marked as M1 and set aside.
[0026] Example 2: Preparation of ferromanganese LDHs dispersion M2
[0027] Manganese nitrate and ferric nitrate are mixed in deionized water to obtain a mixed ion solution, wherein Mn 2+ The concentration of Fe is 0.5 mol / L. 3+ The concentration is 0.25 mol / L; the mixed ion solution is mixed with an equal volume of a NaOH solution with a concentration of 0.75 mol / L, and then sodium nitrite is added to mix and the concentration of nitrite is adjusted to 0.2 mol / L; the mixture is placed in a hydrothermal reactor and subjected to a hydrothermal reaction at 110°C for 7 hours. After cooling to room temperature, the mixture is filtered, washed with water until neutral, and dried at 100°C for 8 hours to obtain ferromanganese LDHs with a particle size of 50 to 110 nm.
[0028] 2 g of ferromanganese LDHs prepared by the above method was dispersed in 40 ml of acetone, stirred at high speed and then ultrasonically dispersed for 15 min, and marked as M2 for later use.
[0029] Example 3: Preparation of ferromanganese LDHs dispersion M3
[0030] Manganese sulfate and ferric nitrate are mixed in deionized water to obtain a mixed ion solution, wherein Mn 2+ The concentration of Fe is 0.4 mol / L, 3+ The concentration is 0.2mol / L; the mixed ion solution is mixed with an equal volume of a NaOH solution with a concentration of 0.6mol / L, and then sodium nitrite is added to mix and the concentration of nitrite is adjusted to 0.15mol / L; placed in a hydrothermal reactor, hydrothermally reacted at 110°C for 8h, cooled to room temperature and then filtered, washed with water until neutral, and dried at 100°C for 8h to obtain manganese iron LDHs with a particle size of 50-120nm.
[0031] 2 g of ferromanganese LDHs prepared by the above method was dispersed in 40 ml of acetone, stirred at high speed and then ultrasonically dispersed for 15 min, and marked as M3 for later use.
[0032] Example 4: Preparation of ferromanganese LDHs dispersion M4
[0033] Manganese sulfate and ferric nitrate are mixed in deionized water to obtain a mixed ion solution, wherein Mn 2+ The concentration of Fe is 0.4 mol / L, 3+ The concentration is 0.25 mol / L; the mixed ion solution is mixed with an equal volume of a NaOH solution with a concentration of 0.65 mol / L, and then sodium nitrite is added to mix and the concentration of nitrite is adjusted to 0.2 mol / L; placed in a hydrothermal reactor, hydrothermally reacted at 120°C for 7 hours, cooled to room temperature and then filtered, washed with water until neutral, and dried at 100°C for 8 hours to obtain manganese iron LDHs with a particle size of 50-120 nm.
[0034] 2 g of ferromanganese LDHs prepared by the above method was dispersed in 40 ml of acetone, stirred at high speed and then ultrasonically dispersed for 15 min, and marked as M4 for later use.
[0035] Comparative Example 1: Preparation of Cobalt-Iron LDHs Dispersion C1
[0036] Cobalt nitrate and ferric sulfate are mixed in deionized water to obtain a mixed ion solution, wherein Co 2+ The concentration of Fe is 0.6 mol / L. 3+ The concentration of the mixed ion solution is 0.2mol / L; the mixed ion solution is mixed with the NaOH solution with a concentration of 0.8mol / L in equal volumes, and then sodium nitrite is added to the mixture to adjust the NO2 - The concentration is 0.2 mol / L; it is placed in a hydrothermal reactor and hydrothermally reacted at 125°C for 7 hours. After cooling to room temperature, it is filtered, washed with water until neutral, and dried at 100°C for 8 hours to obtain cobalt-iron LDHs with a particle size of 100-120 nm.
[0037] 2 g of the cobalt-iron LDHs prepared by the above method was dispersed in 40 ml of γ-butyrolactone, and then ultrasonically dispersed for 15 min after high-speed stirring. The mixture was marked as C1 and set aside.
[0038] Example 5
[0039] Take 75g of polyurethane modified acrylic prepolymer, 25g of ethylene glycol diacrylate (HDDA), and ferromanganese LDHs dispersion M1, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0040] Example 6
[0041] Take 80g of polyurethane modified acrylic prepolymer, 20g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M1, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0042] Example 7
[0043] Take 80g of polyurethane modified acrylic prepolymer, 20g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M2, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0044] Example 8
[0045] Take 85g of polyurethane modified acrylic prepolymer, 15g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M2, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0046] Example 9
[0047] Take 85g of polyurethane modified acrylic prepolymer, 15g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M3, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0048] Example 10
[0049] Take 90g of polyurethane modified acrylic prepolymer, 10g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M3, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0050] Embodiment 11
[0051] Take 80g of polyurethane modified acrylic prepolymer, 20g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M4, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0052] Example 12
[0053] Take 90g of polyurethane modified acrylic prepolymer, 10g of ethylene glycol diacrylate, and manganese iron LDHs dispersion M4, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0054] Comparative Example 2
[0055] Take 75g of polyurethane modified acrylic prepolymer, 25g of glycerol triacrylate, and manganese iron LDHs dispersion M1, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0056] Comparative Example 3
[0057] Take 75g of polyurethane modified acrylic prepolymer, 25g of ethylene glycol diacrylate, and cobalt iron LDHs dispersion C1, mix them and stir them at high speed, then add 5g of active diluent pentaerythritol triacrylate, 2g of filler magnesium oxide, and 2g of BYK163 dispersant, and disperse them in a high-speed disperser at 2500rpm for 80 minutes to obtain the product.
[0058] Example 9
[0059] The coatings prepared in Examples 5-12 and Comparative Examples 2-3 were applied to the surface of the pretreated PMMA blister sheet with a coating thickness of 100 μm, and then cured by electron beam radiation in a nitrogen environment.
[0060] Electron beam radiation curing conditions: curing was performed under the conditions of radiation voltage 400KeV, electron accelerator transmission speed 200m / min, beam current 100mA, electron beam dose 40KGy, nitrogen concentration 200mg / L, and curing temperature 25°C. PMMA blister sheet coatings of each group were obtained respectively.
[0061] The adhesion between the coating and the plate in each embodiment group and the comparative example group reached level 0-1. The hardness of the coating in each group increased with the increase of the prepolymer ratio. Replacing the grafting monomer from ethylene glycol diacrylate to glycerol triacrylate significantly reduced the hardness of the coating. Replacing the LDHs material with cobalt iron LDHs had no effect on the hardness of the coating.
[0062] Table 1 Adhesion and hardness of each group of PMMA blister sheet coating
[0063] Group Example Prepolymer / g Grafted monomer / g LDHs / g Adhesion Pencil hardness I-1 5 75g HDDA25g M12g Level 0 3H I-2 6 80g HDDA20g M12g Level 0 4H I-3 7 80g HDDA20g M22 Level 0 4H I-4 8 85g HDDA15g M22 Level 1 4H I-5 9 85g HDDA15g M32g Level 0 4H I-6 10 90g HDDA10g M32g Level 1 5H I-7 11 80g HDDA20g M42 Level 0 4H I-8 12 90g HDDA10g M42 Level 1 5H I-9 Comparative Example 2 75g Glyceryl triacrylate 25g M12g Level 1 1H I-10 Comparative Example 3 75g HDDA25g C12g Level 0 3H
[0064] Example 10
[0065] Automobile interior materials will gradually age due to frequent exposure to sunlight and drastic temperature changes, and are prone to cracking, thermal expansion and contraction damage, surface roughness or easy damage, etc. Therefore, the focus of this example is to test the wear resistance and scratch resistance of each group of PMMA blister sheet coatings obtained in Example 9 at -20°C and 70°C.
[0066] Table 2 Wear resistance and scratch resistance of each group of PMMA blister sheet coatings
[0067]
[0068]
[0069] It can be seen from Table 2 that the coatings of each embodiment group of the present invention can achieve excellent wear resistance and scratch resistance under high and low temperature conditions.
[0070] RCA wear test: wear tester, load 175g. Wear times classification: Grade A ≥ 4500 times, 4500 times > Grade B ≥ 3000 times, 3000 times > Grade C ≥ 2000 times, 2000 times > Grade D ≥ 1000 times, Grade E < 1000 times.
[0071] Scratch resistance test: GB / T9279.1-2015. Use an automatic constant scratch tester and record the load in N.
[0072] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on some of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An EB coating for automotive interior, characterized in that The invention comprises polyurethane modified acrylic prepolymer, ethylene glycol diacrylate grafted monomer and manganese iron LDHs; wherein, by weight, the amount of polyurethane modified acrylic prepolymer is 50-90 parts, the amount of ethylene glycol diacrylate grafted monomer is 5-25 parts, and the amount of manganese iron LDHs is 0.1-1 parts; the manganese iron LDHs is a layered double metal hydroxide obtained by hydrothermal reaction of manganese salt and trivalent iron salt under the action of NaOH and sodium nitrite.
2. The EB coating for automotive interior according to claim 1, characterized in that The polyurethane modified acrylic prepolymer is used in an amount of 70-85 parts, preferably 75-85 parts.
3. The EB coating for automotive interior according to claim 1, characterized in that The ethylene glycol diacrylate grafting monomer includes ethylene glycol diacrylate, diethylene glycol diacrylate or triethylene glycol diacrylate, and the usage amount thereof is 10-25 parts, preferably 15-25 parts.
4. The EB coating for automotive interior according to claim 1, characterized in that The dosage of the ferromanganese LDHs is 0.5-1 part.
5. The EB coating for automotive interior according to claim 1, characterized in that The preparation method of the ferromanganese LDHs is as follows: manganese salt and trivalent iron salt are mixed in deionized water, and then NaOH solution and sodium nitrite are added to mix, and then placed in a hydrothermal reactor, hydrothermally reacted at 100-125° C., filtered after the reaction, and dried at 90-110° C. to obtain the LDHs.
6. The EB coating for automotive interior according to claim 1 or 5, characterized in that The manganese salt is manganese nitrate or manganese sulfate, and the trivalent iron salt is ferric sulfate or ferric nitrate.
7. The EB coating for automotive interior according to claim 5, characterized in that After manganese salt and trivalent iron salt are mixed in deionized water, Mn 2+ The molar concentration of Fe 3+ The amount of NaOH used is 2-3 times that of Mn 2+ with Fe 3+ 1-1.2 times the sum of the molar amounts, Mn 2+ with Fe 3+ The sum of the molar amounts is 3-4 times the molar amount of sodium nitrite.
8. The EB coating for automotive interior according to claim 1, characterized in that The ferromanganese LDHs are dispersed in a ketone or ester solvent, preferably acetone or γ-butyrolactone.
9. The EB coating for automotive interior according to claim 1, characterized in that It also includes one or more of active diluents, fillers, dispersants, and additives; preferably, it also includes 5-25 parts of active diluents, 1-5 parts of fillers, 1-5 parts of dispersants, and 0.5-2 parts of additives.
10. The EB coating for automobile interior according to claim 1, characterized in that The preparation method comprises: firstly mixing polyurethane modified acrylic prepolymer, ethylene glycol diacrylate grafting monomer and manganese iron LDHs dispersion and then stirring at high speed, or subsequently adding one or more of active diluent, filler, dispersant and auxiliary agent, dispersing in a high-speed disperser at 1500-2500rpm for 20-100 minutes to obtain the product.
Citation Information
Patent Citations
Layered double hydroxide and preparation method thereof
CN101665233A
Electron beam curing coating
CN105440933A
EB-cured wear-resistant coating
CN111534201A
Sealing material and preparation method and application thereof
CN116178863A
UV curing coating composition applied to galvanized sheet
CN116376438A